The Mesoproterozoic thermal evolution of the Musgrave Province in central Australia - Plume vs. the geological record - Smithies, R.; Kirkland, Chris; Korhonen, F.; Aitken, A.; Howard, H.; Maier, W.; Wingate, M.; Quentin de Gromard, R.; Gessner, K. (Elsevier Inc., 2015)
The >1090 to <1040Ma Giles Event added extraordinary volumes of mantle derived magma to the crust of the Musgrave region of central Australia. This included one of Earth's largest mafic intrusions - the Mantamaru intrusion - and the c. 1075Ma formation of the Warakurna large igneous province, which spread dolerite intrusions across ~1.5millionkm2 of western and central Australia. It also included one of the most voluminous additions of juvenile felsic material to Earth's crust, with the development of one of the world's longest-lived rhyolitic centres, including the Talbot supervolcano. Previous suggestions that the event was the result of a deep mantle plume cannot adequately account for the >50m.y. duration of mantle derived magmatism or the fact that isolated localities such as the Talbot Sub-basin preserve the entire magmatic record, with no discernible regional age progressive spatial trend. For at least 100m.y. before the Giles Event, the Musgrave region experienced high- to ultra-high crustal temperatures - possibly as an ultra-hot orogen born from a c. 1300Ma back-arc. Granitic magmatism prior to the Giles Event also involved a significant mantle-derived component and was accompanied by mid-crustal ultra-high temperature (>1000°C) metamorphism reflecting a thin and weak lithosphere. This magmatism also resulted in a mid-crustal (~25km deep) layer greatly enriched in radiogenic heat producing elements that strongly augmented the already extreme crustal geotherms over a prolonged period. The Giles Event may have been triggered when this regional Musgrave thermal anomaly was displaced, and again significantly destabilised, along the Mundrabilla Shear Zone - a continent-scale structure that juxtaposed the Musgrave Province against the easterly extension of the Capricorn Orogen where pre-existing orogen-scale structures were in extension. These orogen-scale structures funnelled the magmas that produced the Warakurna large igneous province and the intersection of the Musgrave thermal anomaly and the Mundrabilla Shear Zone was the site of the Talbot supervolcano. Although previously thought to be a result of a deep mantle plume, the Giles Event was more likely the product of intra-plate tectonic processes involving an anomalous and prolonged thermal pre-history, a magma-focussing lithospheric architecture and large-scale tectonic movements.